Implementation of Air Defense Policy to Prepare Master's Graduates: from Strategic Objectives to Operational Realities - Asep Kurnia; Kemalsyah Kemalsyah; Bambang Kustiawan (Jurnal Indonesia Sosial Teknologi, 2025)
Effective implementation of air defense policy requires careful navigation between clear strategic objectives and the involvement of competent executing agents. This research undertakes a comprehensive evaluation of the key challenges in implementing air defense policy, with a focus on preparing master's graduates to be effective change agents in translating strategy into successful operational actions. Through a targeted qualitative approach and in-depth analysis, the research findings highlight the crucial role of clarity in objectives and standards in formulating effective policies. Constraints such as limited Resources and competency variations are major focal points, which can only be addressed through a holistic and integrated approach. Strong communication, efficient coordination, and steadfast commitment from executing agents are key to successfully navigating complex external dynamics. Research recommendations aim to strengthen master's education, develop technical and managerial competencies, and foster close collaboration with the defense industry to ensure responsive and efficient policy implementation. With an awareness of the complexity of the challenges faced, this research inspires strategic steps that enable the implementation of adaptive air defense policies aligned with national defense objectives.